PENGEMBANGAN SOFT SKILL DIGITAL DAN KECERDASAN EMOSIONAL SEBAGAI STRATEGI PREVENTIF TERHADAP KENAKALAN REMAJA DI ERA DIGITAL - Endi Sutrisna Sutrisna; Nono Suhada; Dethia HS Suci Nurani; Marpuah; Mutoharoh; Anton Nasrullah (Abdimas Aswaja: Jurnal Pengabdian Masyarakat, 2026)
Teenage soft skills training as part of community service activities, in the form of soft skills and leadership training for teenagers at SMAN 9 Pandeglang. The focus of the activity is developing digital soft skills and emotional intelligence (EQ) as preventive capital to face juvenile delinquency and drug abuse amidst rapid social changes and life pressures. The method used is a participatory workshop involving 50 students with structured material on preventing juvenile delinquency and developing self-skills that utilize social media positively. The results of the activity show an increase in participants' awareness regarding the importance of emotion management, digital empathy, and strategies to adapt to digital era challenges. This article concludes that an intervention approach that integrates digital literacy with EQ-based character education is a relevant and effective strategy to strengthen adolescents' psychosocial resilience.